Practical prescribed time control for state constrained systems with event‐triggered strategy: Settling time regulator‐based approach - Zhang, Jie; Yang, Jing; Zhang, Zhongcai; Wu, Yuqiang (International journal of robust and nonlinear control, 2023)
In this article, the practical prescribed time tracking problem based on event‐triggered control is studied for a class of uncertain nonlinear systems subject to asymmetric state constraints. We design a settling time regulator to get a performance function. Using this function, an event‐triggered adaptive control method is put forward for acquiring specified tracking precision in the prescribed time. Then, the asymmetric state constraints are handled by introducing a novel nonlinear state‐dependent function. In combination with backstepping technique, we construct a coordinate transformation to convert the original state‐constrained space into free space. Besides, a dynamic surface control is proposed to eliminate the demanding feasibility conditions on virtual controllers. The communication between controller and actuator is reduced by adopting the appropriate event‐triggered strategy. Moreover, it is indicated that, without altering the control structure, not only the settling time and tracking precision can be selected by the user but also asymmetric state constraints are satisfied. Simulation examples confirm the effectiveness of the presented control scheme.